As condições de trabalho dos (as) assistentes sociais do Centro de Referência Especializado de Assistência Social da Prefeitura Municipal de São Bernardo do Campo – SP - Masuet, Letícia (2022)
This master's dissertation aimed to research, problematize and deepen the working conditions of social workers at the Specialized Reference Center for Social Assistance in the town of São Bernardo do Campo. For this study, a bibliographic review was carried out having Marxian works as reference, as well as the consultation and analysis of dissertations and theses. A qualitative field research with the social workers in question was also conducted, following the regulations stipulated by the Ethics Committee. In the first chapter, it was necessary to bring back the key elements of wage labour in Marx, as well as the process of valorisation and its determinants for the understanding of the contemporary phenomena of workforce exploitation introduced by productive restructuring and its impacts on public services. In the second chapter, the discussion of the worker's health field was made in relation to the workhealth process, emphasizing work in services. In the third and last chapter, the data collected through field research was presented through the instruments of self-completion questionnaires and semi-structured interviews, bringing to light the perception of social workers regarding working conditions, the means necessary for their accomplishment and the health-illness processes. In the analysis undertaken, it is concluded that changes in the management and organization of work in the public service, which are based on neoliberal rationality, change the nature of the service, affecting health and work relationships. This fact indicates that public workers experience working conditions typical of wage relations as members of the working class